Sports Betting Has Gone Virtual: A Sociological Analysis of a New Form of Sports Betting Among Youths in Northern Nigeria - Abdullahi Muhammad; Uthaman Abdullahi Abdul-Qadir; Usman Ahmad Karofi; Umar Dantani (Asosiasi Profesi Pendidik dan Peneliti Sosiologi Indonesia (AP3SI), 2022)
The paper examined the rise of virtual sports betting among football bettors in Northern Nigeria. The study aims to examine the level of penetration of virtual betting and identify the reasons for the development. The researcher adopted Instant Gratification Model to explain the shift from betting on real-time sports betting to virtual betting in the areas selected for the study. The study has adopted a cross-sectional study design, and data were elicited through mixed methods (qualitative and quantitative). Thirteen interviews were conducted: Six Key Informant Interviews (KII) and seven In-Depth Interviews (IDI) with the sports bettors & operators of sports betting outlets. For the quantitative data, 927 structured questionnaires were administered, while 685 were retrieved from the respondents, indicating a 74% response rate. Qualitative data are presented in a prose style, while quantitative data are presented in a tabular form, of frequency tables and cross-tabulation based on the study's objectives. The study found that most virtual sports bettors were youth and educated. It also found that the availability of virtual sports betting 24 hours, unlike actual sporting events, has been identified as one factor that motivates football bettors or gamblers to shift their attention to virtual betting. Furthermore, it found that there are other virtual sporting events like Dog Race and Basketball that attract the bettors' attention to virtual betting. Additionally, the time to finish a virtual football match of fewer than three minutes is also one of the reasons that sports bettors patronize virtual betting because they do not need to wait for 90 minutes to know their fate as in an accurate football match.